Effect of Depo Medroxsi Progesteron Acetat (DMPA) on Indeks Apoptosis Ovarium in The Exposed Rated Endometrium (Rattus Novergicus) - Rizki Fitrianingtyas; Indah Christiana (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
Introduction: Depo Medroxiprogesterone Asetat is the type contraceptive containing only progestin are granted every 3 months that which are considered most effective and regarded with few side effects directly. Side effects long-term that of them , drought the vagina, decrease in the libido , decrease Bone Mineral Density .This caused by because of a decrease in function in the ovary due to the occurrence of apoptosis. Objective: To prove the influence of DMPA with index apoptosis on the ovaries Rattus Norvegicus based on for too long a time exposure to. Methods: Design that is used of these tests are true experiment with the selection in the entire house hold sample use the design of randomized post test drives in cotrol group including on the instrument types. Samples from 30 the tail of a rat males or the two females was classified into 3 group . Group stage matches at first one is the control group (KN) , a second group are to supply 1 treatment being handed out by the provision of therapy DMPA every 1 weeks for rp as long as 1 the month and within a group the third of which was included in the research sample oil which is injected DMPA every once a week for 2 months. Apoptosis index observed with a method of tunel assay kit and a cell that mediate apoptosis in an analysis using a microscope olympus and counting olyvia use . Result : The research results show (p value < 0.05) which means differ significantly . Apoptosis index to 2 are more large treatment from a group 1 and the group one standings larger than the express group control . Estradiol serves as a control an increase in antioxidant genes an enzyme that is an enzyme superoksidase dismutase (SOD) which was with in the mitochondria as a result estradiol can not fulfill their function as antioxidant .The state of this caused the oksidative strees characterized the emergence of free radical. Free radical causes oxidative modification cellular macromolecules , impeding the function of proteins and increase mediate apoptosis. Conclusion: the injections DMPA able to increase apoptosis index in the ovary.